2019
DOI: 10.1177/1945892419887895
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Efficacy of Olfactory Training as a Treatment for Persistent Olfactory Loss

Abstract: Background Among emerging therapies, olfactory training (OT) has been proposed as a potential treatment for persistent olfactory loss. This treatment has been suggested to improve olfactory function via sensorineural modulation from repeated odor exposure. However, due to the long treatment period that is required, many patients discontinue the treatment or do not follow the treatment regimen appropriately, potentially biasing estimates of treatment success. Moreover, spontaneous improvement is known to occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…1 ). Thirteen articles met the criteria for qualitative analysis 29 , 30 , 31 , 32 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 and 6 of these were included in the meta‐analysis. 29 , 30 , 31 , 32 , 33 , 36 All 13 articles reported the distribution of sex, a total of 565 females and 403 males, skewing toward female patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Thirteen articles met the criteria for qualitative analysis 29 , 30 , 31 , 32 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 and 6 of these were included in the meta‐analysis. 29 , 30 , 31 , 32 , 33 , 36 All 13 articles reported the distribution of sex, a total of 565 females and 403 males, skewing toward female patients.…”
Section: Resultsmentioning
confidence: 99%
“…Four articles were randomized controlled trials, 29 , 37 , 38 , 39 assessed by the Cochrane Collaboration's tool, which was shown in Figure 2 . Nine articles were cohort studies, 30 , 31 , 32 , 33 , 36 , 40 , 41 , 42 , 43 assessed by the Newcastle‐Ottawa Scale (Table 3 ). The main sources of bias in these studies were ascertainment of exposure and comparability.…”
Section: Resultsmentioning
confidence: 99%
“…Adherence to the OT intervention will be documented in an Odor training diary ( P.R.O-V1.1E, 2020 ). By one side, some protocols in literature ( Table 1 ) performed the training sessions twice a day or 12 weeks of OT ( Hummel et al, 2009 ; Haehner et al, 2013 ; Schriever et al, 2014 ; Fornazieri et al, 2019 ). However, by other side, Schriever et al (2014) and Fornazieri et al (2019) have indicated that only half part of the sample strictly follow the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…By one side, some protocols in literature ( Table 1 ) performed the training sessions twice a day or 12 weeks of OT ( Hummel et al, 2009 ; Haehner et al, 2013 ; Schriever et al, 2014 ; Fornazieri et al, 2019 ). However, by other side, Schriever et al (2014) and Fornazieri et al (2019) have indicated that only half part of the sample strictly follow the protocol. In this regard, our main objective is to propose a protocol that can be followed in an easy and manageable way by our sample of very old adults.…”
Section: Methodsmentioning
confidence: 99%
“…Fornazieri et al. evaluated olfactory training in a prospective observational study 8 and found that the effectiveness of olfactory training in their population approximated or was worse than that expected from spontaneous recovery alone 9,10 . In addition, adherence was relatively low when patients did not experience noticeable improvements within the first 3 months 8 …”
mentioning
confidence: 99%